2014
DOI: 10.1103/physreve.90.062310
|View full text |Cite
|
Sign up to set email alerts
|

Echoes in x-ray speckles track nanometer-scale plastic events in colloidal gels under shear

Abstract: We report x-ray photon correlation spectroscopy experiments on a concentrated nanocolloidal gel subject to in situ oscillatory shear strain. The strain causes periodic echoes in the speckle pattern that lead to peaks in the intensity autocorrelation function. Above a threshold strain that is near the first yield point of the gel, the peak amplitude decays exponentially with the number of shear cycles, signaling irreversible particle rearrangements. The wave-vector dependence of the decay rate reveals a power-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 54 publications
2
28
1
Order By: Relevance
“…There is increasing evidence to suggest that the microscopic mechanism of plastic deformation is a local rearrangement of particles involving a change of nearest neighbours (so called shear transformation zones), which results in an Eshelby-like elastic field 2 3 4 5 . However, it was recently shown that these rearrangements can be repetitive or irreversible depending on the strain amplitude 6 7 8 9 10 11 12 13 14 15 16 17 18 (a similar phenomenon has been observed in the shearing of colloidal suspensions, granular systems, dislocations and super-conducting vortices 19 20 21 22 23 24 25 26 27 28 and in the compaction of granular matter 29 ).…”
mentioning
confidence: 80%
“…There is increasing evidence to suggest that the microscopic mechanism of plastic deformation is a local rearrangement of particles involving a change of nearest neighbours (so called shear transformation zones), which results in an Eshelby-like elastic field 2 3 4 5 . However, it was recently shown that these rearrangements can be repetitive or irreversible depending on the strain amplitude 6 7 8 9 10 11 12 13 14 15 16 17 18 (a similar phenomenon has been observed in the shearing of colloidal suspensions, granular systems, dislocations and super-conducting vortices 19 20 21 22 23 24 25 26 27 28 and in the compaction of granular matter 29 ).…”
mentioning
confidence: 80%
“…At sufficiently high strains (γ 0 > 0.01-0.02), crystal clusters begin to break up and/or become aligned by the shear flow as stress decays (I 3 / 1 keeps increasing or drops). The prevalence of a double-arc shape in I 3 / 1 in some samples might be attributed to two separate yielding processes, as observed in some concentrated colloidal gel or shear instabilities (Wilhelm et al 1999;Rogers et al 2014). To describe the evolution of I 3/1 , we used a descriptive function proposed by Wilhelm et al (2000).…”
Section: Nonlinear Viscoelasticitymentioning
confidence: 99%
“…Whereas γ × is frequently quoted as "the" yielding point in the literature, a stress overshoot also serves to identify yielding in shear-start experiments [25]. A stress overshoot is reported in some oscillatory shear experiments [19], but is absent in others [12,13]. A possible explanation is that experiments are typically performed at somewhat larger frequencies, where additional contributions to the shear stress (lubrication forces, hydrodynamic effects) might hide this behaviour.…”
Section: Smooth Crossover In Macroscopic Rheologymentioning
confidence: 99%